Nanoformation in doped silicate glass and its fractal dimensions - L. A. Bulavin; S. O. Samoilenko; S. E. Kichanov; D. P. Kozlenko; O. I. Ivankov; V. S. Gurin; G. E. Rachkovska; G. B. Zaharevych; A. Kh. Islamov; B. N. Savenko (Ядерна фізика та енергетика)
PbS nanostructures in silicate glasses under different conditions of heat treatment were investigated using small-angle neutron scattering. It was found that spherical nanoparticles with radii of 3.0 nm to 3.9 nm are forming in these glasses. The increase of the average size of nanoparticles and changes in the fractal dimension of glass samples under increasing heat treatment time are observed. The structural model of the formation mechanism of PbS nanoparticles in a glass matrix during its thermal treatment is discussed.